2019
DOI: 10.1093/gigascience/giz029
|View full text |Cite
|
Sign up to set email alerts
|

An efficient and robust laboratory workflow and tetrapod database for larger scale environmental DNA studies

Abstract: Background The use of environmental DNA for species detection via metabarcoding is growing rapidly. We present a co-designed lab workflow and bioinformatic pipeline to mitigate the 2 most important risks of environmental DNA use: sample contamination and taxonomic misassignment. These risks arise from the need for polymerase chain reaction (PCR) amplification to detect the trace amounts of DNA combined with the necessity of using short target regions due to DNA degradation. Findings… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
77
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 42 publications
(77 citation statements)
references
References 70 publications
0
77
0
Order By: Relevance
“…Data on the life history and behavior of leeches would also be needed to interpret the results, such as the time interval between feeding and sampling (Schnell et al, ). However, the studies in Vietnam, Bangladesh and Borneo indicated that the hosts were taxonomically variable (Axtner et al, ; Schnell et al, ; Weiskopf et al, ), so other Haemadipsa leeches might be suitable for making a species inventory.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Data on the life history and behavior of leeches would also be needed to interpret the results, such as the time interval between feeding and sampling (Schnell et al, ). However, the studies in Vietnam, Bangladesh and Borneo indicated that the hosts were taxonomically variable (Axtner et al, ; Schnell et al, ; Weiskopf et al, ), so other Haemadipsa leeches might be suitable for making a species inventory.…”
Section: Discussionmentioning
confidence: 99%
“…Another relatively unexplored topic is on how different analysis method affects the results. Next generation sequencing (NGS) technology has been applied in the iDNA studies (Abrams et al, 2019;Axtner et al, 2019;Calvignac-Spencer, Merkel, et al, 2013b). One obvious advantage of NGS is that it can detect the DNA of multiple species collected from one individual of an invertebrate.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Samples were stored in RNA fixating saturated ammonium sulfate solution and exported under the permit 'JKM/MBS.1000-2/3 JLD.2 (8)' issued by the Sabah Biodiversity Council. A total of 68 pools (L1-L68) were selected for viral capture to maximize representation of host wildlife species identified from bloodmeals [31].…”
Section: Sample Collectionmentioning
confidence: 99%
“…Host identification of leeches followed an eDNA/iDNA workflow recently published [31]. In summary, leech samples were digested and short fragments of the mitochondrial markers 12S, 16S and cytochrome B were amplified in four PCR replicates each resulting in 12 PCR replicates per sample.…”
Section: Leech Vertebrate Host Assignmentsmentioning
confidence: 99%